Canadian Women Composers in Modernist Terrain: Violet Archer, Jean Coulthard and Barbara Pentland - Danielson, Janet (Circuit, 2009)
The successful compositional careers of Jean Coulthard, Barbara Pentland, and Violet Archer spanned all but the first three decades of the twentieth century. Entering a compositional career at this time had many challenges: as Western Canadians, these composers had to establish their credibility with a public that could not be counted on to recognize the worth of their work due to sexist bias and a prevailing critical stance: public approval was evidence of a lack of true creativity. This was especially problematic for women, who had to keep to the center of progressive composition, away from the experimental and conservative margins, in order to gain recognition. Following World War II, the pressure of modernism increased, due at least in part to initiatives by the U. S. Government in occupied Germany, countering the stereotype of the unsophisticated American with a new narrative of American experimental tradition.
Publisher: Les Presses de l'Université de Montréal

The Piano Sonatas of Violet Archer: The Creative Influences of Bartók and Hindemith - Friesen, Darryl Shane (Université de l'Illinois à Urbana-Champaign, 2009)

Introduction : Compositrices sur la scène contemporaine - Goldman, Jonathan (Circuit: Musiques contemporaines, 2009)

Micheline Coulombe Saint-Marcoux et Marcelle Deschênes : pionnières dans le sentier de la création électroacoustique - Lefebvre, Marie-Thérèse (Circuit : musiques contemporaines, 2009)
A review of “masculine” and “feminine” attitudes towards music composition of the past fifty years highlights the contributions of Micheline Coulombe Saint-Marcoux and Marcelle Deschênes to the development of Québécois electroacoustic music. The author re-creates the historical context for the composers’ childhoods, adolescences, and periods of training in Montreal and Paris, and follows this with a discussion of how they negotiated the dominant trends of the 1970s. She then turns to the composers’ roles as pioneers: in their wish to depart from well-trodden paths, Coulombe Saint-Marcoux and Deschênes turned to new technological tools that would allow them to express a new artistic sensibility. From this perspective, they should be considered the “sherpas” of Québécois electroacoustic music.
Publisher: Les Presses de l'Université de Montréal

Hildegarde von Bingen et Lorraine Vaillancourt : deux femmes rebelles dans leur siècle... - Peillon, Catherine (La pensée de midi, 2009)
Bibliographie_available: 0 Cairndomain: www.cairn.info Cite Par_available: 0 Publisher: Actes sud

Des pratiques d’artistes et de chercheuses en écologie sonore - Piché, Claire (Recherches féministes, 2009)
This article is an incursion into the domain of sound ecology based on interdisciplinary research about artists and researchers. We expose the fundamental principles of sound ecology, a discipline that emerged during the seventies, and discuss the best practices of women in sound ecology, demonstrating how this constitutes a relevant research area for women’s studies. The link between feminism and sound ecology being established, we summarize three sociopolitically relevant research projects whose methods resemble feminist action research. We conclude by reflecting on the best means to foster interdisciplinary collaboration.
Publisher: Revue Recherches féministes

De la musique de geste à la musique du son, de SuperMémé à I8U - Prévost, Hélène (Circuit, 2009)
La musique actuelle née au tournant des années 1970-1980 a connu ses heures de gloire pendant de nombreuses années. Trois femmes font partie de la lancée et demeurent à ce jour des musiciennes actives et des administratrices hors pair. Mais d’autres, artistes sonores plutôt qu’instrumentistes, émergent, au moment du tournant technologique et plus particulièrement au milieu des années 1990. Un nombre important de ces femmes développent des pratiques non instrumentales d’art audio, de musique bruitiste, de musiques mixtes, électroniques expérimentales, d’installation et de multimédia. Elles sont mal connues, méconnues des grands médias et de la plupart des lieux d’enseignement de la musique, bien que plusieurs d’entre elles les aient fréquentés. Ce moment de rencontre avec certaines d’entre elles souhaite les faire apparaître, en plein jour.
Publisher: Les Presses de l'Université de Montréal

Interpreting success and failure: the eclectic careers of Eva and Juliette Gauthier - Slominska, Anita (Université McGill, 2009)
My dissertation explores the eclectic singing careers of sisters Eva and Juliette Gauthier. Born in Ottawa, Eva and Juliettte were aided in their musical aspirations by the patronage of Prime Minister Wilfred Laurier and his wife Lady Zoë. They both received classical vocal training in Europe. Eva spent four years in Java. She studied the local music, which later became incorporated into her concert repertoire in North America. She went on to become a leading interpreter of modern art song. Juliette became a performer of Canadian folk music in Canada, the United States and Europe, aiming to reproduce folk music “realistically” in a concert setting. My dissertation is the result of examining archival materials pertaining to their careers, combined with research into the various social and cultural worlds they traversed. Eva and Juliette’s careers are revealing of a period of transition in the arts and in social experience more generally. These transitions are related to the exploitation of non-Western people, uses of the “folk,” and the emergence of a cultural marketplace that was defined by a mixture of highbrow institutions and mass culture industries. My methodology draws from the sociology of art and cultural history, transposing Eva and Juliette Gauthier against the backdrop of the social, cultural and economic conditions that shaped their career trajectories and made them possible.

Tunes That Bind: Paul J. Seelig, Eva Gauthier, Charles T. Griffes, and the Javanese Other - Spiller, Henry (Journal of the Society for American Music, 2009)
The powerful concept of orientalism has undergone considerable refinement since Edward Said popularized the term with his eponymous book in 1978. Orientalism typically is presented as a totalizing process that creates polar oppositions between a dominating West and a subordinate East. U.S. orientalisms, however, reflect uniquely North American approaches to identity formation that include assimilating characteristics usually associated with the Other. This article explores the complex relationship among three individuals—U.S. composer Charles T. Griffes, Canadian singer Eva Gauthier, and German-trained Dutch East Indies composer Paul J. Seelig—and how they exploited the same Javanese songs to lend legitimacy to their individual artistic projects. A comparison of Griffes's and Seelig's settings of a West Javanese tune (“Kinanti”) provides an especially clear example of how contrasting approaches manifest different orientalisms. Whereas Griffes accompanied the melody with stock orientalist gestures to express his own fascination with the exotic, Seelig used chromatic harmonies and a chorale-like texture to ground the melody in the familiar, translating rather than representing its Otherness. The tunes that bind Griffes, Gauthier, and Seelig are only the raw materials from which they created their own unique orientalisms, each with its own sense of self and its own Javanese others.
Publisher: Cambridge University Press

La composition musicale et la marque du genre : l’examen conscient de l’« écriture féminine » - Stévance, Sophie (Circuit, 2009)
Si les spéculations idéologiques concernant les différences biologiques entre les sexes persistent dans le domaine de la création, elles ont été mises en valeur dès 1970 par des écrivaines et plasticiennes pour oeuvrer en fonction de mythes spécifiques touchant à leur féminité, au corps de la femme chargé de stigmates, afin qu’émerge un « art féminin ». D’une certaine manière, des compositrices vont emprunter cette voie en affirmant entretenir un rapport différent de celui des hommes à l’écriture musicale. Selon elles, leur sensibilité spécifique et leur situation d’être au monde les poussent à travailler autrement, à partir de thématiques « existentielles » inspirées de leur condition sociale et culturelle. De telles circonstances ont provoqué cette quête identitaire par l’invention d’un style artistique particulier qui, paradoxalement, use de ce qui était considéré par un féminisme radical comme les pièges de la féminité. Cet article tente de montrer que ces spécificités, du moins ces constantes relevées par les créatrices expliquant leur démarche, sont le résultat de recherches esthétiques pour caractériser une création universelle au féminin, et non le produit de diktats biologiques.
Publisher: Les Presses de l'Université de Montréal

Réactiver le sens de l’hommage : L’exemple du Festival SuperMicMac au Canada - Stévance, Sophie (Itamar, 2009)
Cet article étudie la notion d’hommage à partir du Festival SuperMicMac organisé en 2000 par sept compositrices à la mémoire de Mary Travers (alias La Bolduc), icône de la musique populaire au Québec dans les années 1930. Par des allusions, des références précises et explicites ou par de simples emprunts et citations, ces hommages sont autant de lectures que de relectures des chansons sélectionnées en abordant différents modes de jeux d’« intertextualité musicale ». Celle-ci se situe à deux niveaux : le pôle de la production, qui montre que les chansons engagées de La Bolduc sont ellesmêmes le témoignage d’une époque ; le pôle de la réception, pour exposer les résonances de ces chansons à partir de références autres et communes à la fois, comme la place des femmes dans la création musicale. Cette étude envisage ainsi l’hommage à partir des aspects, des significations et des enjeux musicaux posés par l’intertextualité musicale. L’hommage est ainsi conçu comme un « réactivateur » de sens.

Colette Boky. Le chant d'une femme - Boky, Colette; Barrière, Mireille (Éditions Triptyque, 2008)
La présente biographie relate une carrière riche, autant à l'opéra qu'au concert et en récital. Le lecteur pénètre dans les coulisses parfois mystérieuses des maisons d'opéra. Colette Boky nous entretient de ses relations avec ses collègues, de sa conception des principaux rôles qu'elle a incarnés, de ses prestations devant maints personnages célèbres. Mais, plus encore, ces pages tracent le portrait d'une femme résolue, fonceuse, au franc parler, qui ne craint pas de mettre sa réputation au service de causes qui lui tiennent à coeur.

Les femmes et la vie culturelle à Québec avant la Révolution tranquille - Harvey, Fernand (Cap-aux-Diamants : la revue d'histoire du Québec, 2008)

La faim Artaud. Le corps musical éclaté : à la recherche d'un langage musical inspiré d'Artaud - Llugdar, Analia (Université de Montréal, 2008)
Ce travail s'inscrit dans une rechcerche interdisciplinaire tendant à faire le point sur l'actualité de la pensée d'Antonin Artaud à travaers l'analyse du texte radiophonique Pour en finir avec le jugement de dieu. Ce texte conçu peu avant sa mort réunit tous les éléments propres à la pensée d'Artanud tant au niveau philosophique qu'au niveau formel: le corps sans organes, le concept de jugement, l'idée de dieu mais aussi les «sonorisations», les cris et les «glossolalies» à travers une étude profonde des différents textes d'Artaud ainsi que de ses dessins, de sa voix enregistrée, de ses mises en scènes et des différents aspects de son langage, j'ai élaboré une écriture musicale qui m'a permis de composer une oeuvre qui s'inscrit dans le domaine du théatre musical et qui se veut une lecture personnelle d'Artaud. Ainsi, les éléments de ce nouveau langage ont été incorporés aux oeuvres que j'ai composé postérieurement. Nous aborderons dans le chapitre 1 les sourecs nombreuses et hétéroclites du langage d'Artaud; la lecture de ses différentes manières d'expression artistique sont indispensables à la compréhension et à l'interprétation de sa pensée. Le chapitre 2 présente une analyse approfondie de la pièce résultat de ces recherche: La Faim d'Artaud, oeuvre de théatre musical pour sept instrumentistes, mezzo-soprano, baryton, un comédien et une bande pré-enregistrée. Cette analyse montre différents aspects du langage artaudien, présents dans la musique et dans les choix de mise en scène. Le dernier chapitre est une exemplification de l'influence qu'a exercée le langage développé à travers la composition de La Faim d'Artaud dans d'Autres oeuvres de mon répertoire. Pour démontrer cette influence, j'ai réalisé une analyse sommaire de la pièce Todos los recuerdos presentes envolvìan ese sonido y algo me miró pour orchestre de chambre de quinze instrumentistes.

Culture, État et responsabilités : entretien avec Ana Sokolovic - Gendreau, Philippe (Liberté, 2007)
Publisher: Collectif Liberté

Itinéraire de quatre pionnières de la vie culturelle à Québec après 1945 - Harvey, Fernand (Les cahiers des dix, 2007)
À Québec comme partout ailleurs, la place des femmes dans la sphère publique est relativement récente. L’idée qu’une femme puisse poursuivre des études universitaires, travailler à l’extérieur de la maison ou entreprendre une carrière après le mariage a commencé à se généraliser peu avant les années 1960. Dans ce long cheminement, certaines femmes ont joué un rôle pionnier. Cet article examine le parcours de vie de quatre de ces femmes qui ont réussi à faire leur marque dans le milieu culturel et médiatique de la ville de Québec au cours des années qui ont suivi la seconde guerre mondiale : Francoise Larochelle-Roy, Simone Bussières, Georgette Lacroix et Monique Duval. L’itinéraire biographique de ces pionnières permet de mieux comprendre les singularités de leur insertion dans le milieu culturel et professionnel, en même temps que les points communs qui les relient toutes quatre au contexte d’une époque. On les suivra donc depuis l’enfance jusqu’à la vie adulte où elles évolueront dans l’enseignement, le journalisme, l’animation radiophonique, ainsi que dans le monde des lettres.
Number: 61

La rencontre des musiques du Moyen-Orient et de l'Occident : esthétisme, composition et analyse - Makdissi-Warren, Katia (Université de Montréal, 2007)
The object of this dissertation is the meeting of Middle-Eastern and Western music. The dissertation includes an essay and seven original compositions (scores and recordings). The text begins with the exposition of the basics of Middle-Eastern music required to understand my artistic approach. The 'taqasim', a major musical form in the Middle-East and a source of inspiration for my work is presented in more detail. The second chapter deals with the philosophy of aesthetics involved in the intermixing of musical cultures. Concerns about the coherence of commingled languages are exposed. The concepts of intermixing, cultural identity and coherence of a work are submitted for discussion. For a given work, does the notion of coherence retain its essence from one person to the next according to culture and social context? This questioning is directly linked to the creation and generation of the processes of development for the musical material in my compositions. Throughout the chapter, I position my approach in relation to the thinking of authors such as Adorno, but also relative to personal experiences. In chapter 3 I describe the writing processes I have developped in order to create a sound fabric wherein Middle-Eastern music meets that of the West. My work defines processes for treating parameters in order to draw together elements of both Eastern and Western musical expressions into a distinctive language <f> <fr><nu>.</nu><de>7</de></fr></f> the key to this is grasping how one musical element influences another. Using analysis as a starting point for the comparison of musical parameters in each of the languages, I have elaborated new commingling (intermixing) techniques. This chapter is therefore devoted to the cross-relational writing techniques that have been evolved to adequately support my artistic approach. The final chapters of this dissertation feature the detailed analyses of three of my compositions: 'Jet Stream, Algorythme and PLB'. Each piece's form, sections and sub-sections are presented followed by the analysis of its basic musical material and development.

A Queer Protocol of Homage: Chambres de Ténèbres/Tombeau de Claude Vivier By Marko Nikodijević - Novak, Jelena (International Journal of Music New Sound, 2007)
The music of Canadian composer Claude Vivier (1948-1983) was used as a fractalized material for the creation of the composition Chambres de ténèbres/tombeau de Claude Vivier (2005) by Marko Nikodijević. Vivier’s opus and his marginal queer acting were the pillars of Nikodijević’s meticulous reading/deconstructing of Vivier’s world through his own artistic dilemmas.

Jeanne Maubourg (1875-1953) : l’apprentissage de la modernité théâtrale - Robert, Lucie (Jeu. Revue de théâtre, 2007)
Un article de la revue Jeu, diffusée par la plateforme Érudit.

L’opéra pour enfants ou la quête d’identité : commentaire critique sur L’arche, d’Isabelle Panneton et Anne Hébert - Champagne, Éric (Circuit : musiques contemporaines, 2006)
Avant de rendre compte de l’opéra pour enfants L’arche (musique d’Isabelle Panneton, livret d’Anne Hébert), créé le 25 novembre 2004 par le Nouvel Ensemble Moderne et l’Atelier lyrique de l’Opéra de Montréal, cet article replace l’oeuvre dans un contexte plus large en esquissant un portrait de l’opéra pour enfants au XXe siècle. À travers diverses incarnations (parmi lesquelles l’opéra interprété par et pour des enfants), le genre est caractérisé par une durée limitée à moins d’une heure et un sujet spécifiquement destiné aux enfants, rendu aussi compréhensible que possible par un livret écrit dans la langue de son auditoire et porté par une musique claire et simple. Si ces caractéristiques ne vont pas sans soulever quelques questions, l’auteur estime qu’ils trouvent dans L’arche une illustration tout à fait réussie.
Publisher: Les Presses de l'Université de Montréal

Gender, Genre and Electroacoustic Soundmaking Practices - McCartney, Andra (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2006)
This article is an exploration of how genres and practices of electroacoustic soundmaking are gendered, examining processes of gendering in language used in the early dichotomous categorization between musique concrète and elektronische Musik, then thinking about related arguments concerning abstraction, context, and compositional control in the writings of electroacoustic soundmakers including Pierre Schaeffer, Pierre Boulez, Daphne Oram, Pauline Oliveros, and several participants of the In and Out of the Sound Studio project. Analysis of their practices and ideas suggests different ways of conceptualising electroacoustic genres, their related practices, and roles of contemporary electroacoustic soundmakers (composers, artists, producers, mixers, audiences...), by examining the potentials of the concepts of empathetic knowledge and ecological thinking advanced by feminist epistemologist Lorraine Code.

Portrait d’Ana Sokolovic - Picard, Isabelle (Circuit : musiques contemporaines, 2006)
An article from Circuit, on Érudit.
Publisher: Les Presses de l'Université de Montréal

Œuvres principales d’Ana Sokolovic - Picard, Isabelle (Circuit : musiques contemporaines, 2006)
An article from Circuit, on Érudit.
Publisher: Les Presses de l'Université de Montréal

La alegría de hacer música contemporánea: entrevista con Lorraine Vaillancourt [La joie de faire de la musique contemporaine : entretien avec Lorraine Vaillancourt] - Stan, Luana (Doce notas preliminares, 2006)
Publisher: Doce notas Section: Doce notas preliminares: revista de música y arte

Entretien avec Joane Hétu - Arroyas, Frédérique (Critical Studies in Improvisation / Études critiques en improvisation, 2005)

Y a-t-il des créatrices en musique au Québec ? - Carignan, Nicole; Leblanc (FAMEQ à la une, 2005)

Constructions of Identity in the Life Stories of Emma Albani and Glenn Gould - Elliott, Robin (Journal of Canadian Studies, 2005)
Biographical accounts of musicians have enjoyed widespread popularity since the late-Victorian era. Literary theory has recently held biography to be a literary construct, rather than a factual enterprise. Biographies and music are both governed by narrative structures and help to create a sense of individual and collective/national identity. Biographical accounts of two Canadian musicians—Emma Albani and Glenn Gould—are examined. Both musicians are Canadian national icons, but there are several problematic issues in their life stories: Albani’s elitism, class consciousness, and ambiguous relationship to Canada, and Gould’s eccentricity and uncertain sexual identity. The article examines how these issues have been handled in various auto/biographical accounts of the two musicians.
Publisher: University of Toronto Press

The Loudspeaker as Instrument: the soundworks of Nancy Tobin - Friz, Ann (Musicworks, 2005)

Violet Balestreri Archer (1913-2000) - Hartig, Linda (Music Reference Services Quarterly, 2005)
Violet Archer, one of Canada's well-known composers, passed away in 2000. This article is meant to add biographical information not previously available and to bring closure to her works list. Selected bibliographical citations are also included.
Keywords: Canadian composers; Violet Balestreri Archer

La contribution des femmes à l’histoire musicale et les compositrices d’aujourd’hui au Québec - Lefebvre, Marie-Thérèse (L'accès des femmes à l'expression musicale. Apprentissage, création, interprétation. Les musiciennes dans la société contemporaine, 2005)

L’art de chanter… au féminin : de la prise de paroles au jeu de références postmodernes - Oberhuber, Andrea (L’accès des femmes à l’expression musicale. Apprentissage, création, interprétation : les musiciennes dans la cité, 2005)

Diane Leboeuf: from mixing boards to museums - Gasior, Lisa; McCartney, Andra (Musicworks, 2004)

Geneviève Gilardeau : le violon baroque et Jean-Marie Leclair - Melançon, Johanne (Liaison, 2004)
Publisher: Les Éditions l'Interligne

Étude sociologique de la musique actuelle du Québec : le cas des Productions Supermusique et du Festival International de Musique Actuelle de Victoriaville - Robineau, Anne (Université de Montréal, 2004)
Cette thèse a pour but l’étude sociologique de la musique actuelle au Québec. La musique actuelle est une pratique de création créée en dehors des institutions académiques et des centres de recherche. La professionnalisation de ce milieu artistique est décrite et analysée dans une perspective sociologique en prenant les cas des Productions Supermusique et du label DAME ainsi que du festival International de Musique Actuelle de Victoriaville. L’objectif de cette thèse est d’acquérir une connaissance sur la façon dont s’est développé ce milieu musical des années 70 à aujourd’hui.

Violet Archer: Eine sozio-kulturelle Einordnung der Musik der kanadischen Komponistin unter besonderer Ber cksichtigung der Orchesterwerke [Violet Archer : une classification socioculturelle de la musique de la compositrice canadienne, avec une attention particulière à ses œuvres orchestrales] - Glathe, Kerstin (Université de la Ruhr à Bochum, 2003)
Keywords: Pas de lien web

Creating and Contributing: The Expansive Spirit of Marcelle Deschênes - Mountain, Rosemary (Musicworks, 2003)

Maya Badian: Her Life and Her Music, A Privilege to Soar - Popovici, Fred (Editura Muzicalǎ, 2003)

Maryvonne Kendergi. La musique en partage - Bail, Louise (Éditions Hurtubise, 2002)

New Games in the Digital Playground: Women Composers Learning and Teaching Electroacoustic Music - McCartney, Andra (Feminism & Psychology, 2002)
Publisher: SAGE Publications Ltd

Québec, vingtième siècle : La création musicale, une affaire de femmes ? - Galaise, Sophie (Musicanada 2000: A Celebration of Canadian Composers/Un hommage aux compositeurs canadiens, 2001)

Les chants sacrés des Ursulines de Québec à l'époque de Marie Guyart - Courville, Louise (Marie Guyard de l’Incarnation. Un destin transocéanique (Tours, 1599-Québec, 1672), 2000)

Colloquy/Débat: Violet Archer, Jean Coulthard, and Barbara Pentland Remembered - Deaville, James (Canadian University Music Review, 2000)
In a bizarre coincidence, three important Canadian women composers from the same generation recently died within five weeks of each other: Barbara Pentland on 6 February 2000, Violet Archer on 22 February 2000, and Jean Coulthard on 9 March 2000. As a tribute to their lives and work, this colloquy gathers remembrances of them by friends and colleagues, ranging from brief anecdotes to extended memoirs. It is thus a collection of primary documents, which yield many new insights into the lives of our composers, ranging from personal habits to the way they taught composition.
Keywords: Canadian music; Careers; Composers; Composition; Music

L’énigme de la correspondance d’Albani à Heugel - Langlois, Maryse (Les Cahiers de la Société québécoise de recherche en musique, 2000)

Quarante ans au cœur de l'Orchestre symphonique de Montréal - Lyse, Vézina (Varia, 2000)

Emma Albani - Vachon, Pierre (Éditions Lidec, 2000)
Biographie concise sur la carrière d'une illustre compatriote, Emma Lajeunesse dite Albani. Elle fut la première cantatrice québécoise à connaître une renommée internationale.

La carrière d’Emma Albani au Covent Garden de Londres - Vachon, Pierre (Les Cahiers de la Société québécoise de recherche en musique, 2000)